2001
DOI: 10.1038/sj.ijo.0801698
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary fat in the prevention and treatment of obesity. Efficacy and safety of low-fat diets

Abstract: BACKGROUND: Does dietary fat play a central role in weight gain and development of obesity? Do low-fat diets have adverse effects on blood lipids? OBJECTIVE AND DESIGN: To answer these questions we have reviewed the evidence linking the dietary fat content to energy balance and obesity, and examined the efficacy and safety of ad libitum low fat, high carbohydrate=protein diets in the prevention and management of obesity. RESULTS: Physiological studies have provided insight into the mechanisms by which the macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
0
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 19 publications
5
50
0
11
Order By: Relevance
“…A possible explanation for the lack of relationship of food consumption and sedentary activities to obesity in this study might be the study type since cross-sectional studies are weak in such associations. 36 Even recently, a cross-sectional study indicated that energy intake was higher in non-overweight than in overweight children. 37 An interesting finding of the study is the increased risk of offspring obesity in diabetic parents.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the lack of relationship of food consumption and sedentary activities to obesity in this study might be the study type since cross-sectional studies are weak in such associations. 36 Even recently, a cross-sectional study indicated that energy intake was higher in non-overweight than in overweight children. 37 An interesting finding of the study is the increased risk of offspring obesity in diabetic parents.…”
Section: Discussionmentioning
confidence: 99%
“…58 Weight gain can occur in spite of decreased food consumption when on a high-fat diet, perhaps due to differences in the efficiency of storage or thermic effects of digestion. 19,32,58,59 The WD used in this study has very high levels of saturated fats and added sucrose, both of which are considered unhealthy if ingested frequently because they can contribute to the metabolic syndrome and other chronic diseases. The impact this diet would have on health-related traits in these mice has not yet been explored, but the elevated running in HR mice may serve to ameliorate other negative effects of such a diet, much like wheel running reduced body fat in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Astrup [3,4] a fait deux méta-analyses des études d'intervention randomisées, durant plus de deux mois, et comparant une alimentation appauvrie en lipide et une alimentation normale en lipides, excluant toutes celles ou la perte de poids était l'objectif et utilisant un autre moyen de l'obtenir. Qu'il s'agisse des populations d'IMC de 21 à 30, ou de celles d'IMC > 25, la réduction d'environ 10 % de l'apport énergétique sous forme de lipide se traduit par une perte assez reproductible de 2,4 à 3 kg en 6 mois.…”
unclassified
“…D'autres études sont venues confirmer ce phénomène qui est valable en qualité (il y a perte de poids) et en intensité (entre 2,5 et 3 kg en 6 mois). Il concerne des patients en surpoids ou obèses, les intolérants au glucose, les hommes et les femmes [3][4][5]. Cela vaut aussi pour des patients hypercholestérolémiques avec la diète « step 1 » de la NCEP où les lipides saturés sont réduits de 10 %.…”
unclassified